Patient-reported health outcomes in a trial of etanercept monotherapy versus combination therapy with etanercept and methotrexate for rheumatoid arthritis: the ADORE trial. Issue 8 (31st July 2007) - van Riel, P L C M; Freundlich, B; MacPeek, D; Pedersen, R; Foehl, J R; Singh, A; ,
Abstract : Objectives: This study assessed the relative efficacy of etanercept (ETN) or etanercept and methotrexate (ETN+MTX) for patients with rheumatoid arthritis (RA) who had an unsatisfactory response to MTX, using patient-reported outcomes (PROs) of function, pain, general health, disease activity and morning stiffness. Methods: The PROs were secondary assessments in a 16-week, prospective, randomised, parallel-group study conducted at 60 European centres. Patients with RA were randomly assigned either to monotherapy with ETN or combination therapy with ETN+MTX. PRO instruments administered included the Stanford Health Assessment Questionnaire, the pain visual analogue scale, the EuroQoL assessment of current health state (EQ-5D), the EQ-5D visual analogue scale, a patient global assessment of disease activity and an assessment of morning stiffness. Treatment groups were compared by percentage of patients within clinically meaningful categories. The primary endpoint for all PROs was comparison of mean improvement from baseline to week 16 between ETN and ETN+MTX groups. Results: Three hundred and fifteen patients were randomised to ETN or ETN+MTX. Both treatment arms had similar Health Assessment Questionnaire Disability Index DI, EQ-5D, patient global assessment of disease activity, pain or morning stiffness scores and improvement from baseline to week 16. Conclusions: For patients with active RA and intolerance or unsatisfactory response to MTX, substituting ETN for MTX and adding ETN to MTX are both effective ways of reducing disability, pain, disease activity, morning stiffness, and improving general health.